Strategic enhancement of local taxing power: A Comprehensive SWOT analysis approach - Kuncoro, Antonius Ragil; Roberta (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2025)
Strengthening local taxing power is a crucial element in addressing the insufficient capacity of regional governments to manage their regional assets effectively. This study seeks to identify approaches for strengthening local taxing authority within local administrations. Employing a case study methodology, the research focused on the Jombang regional government, which has a regional tax ratio of 0.6%, significantly lower than the 3% benchmark established by the Ministry of Finance. A content analysis of the data was performed to identify the Strengths, Weaknesses, Opportunities, and Threats (SWOT) in strategy development. The findings suggest that the advised strategy falls within Quadrant I, representing the Strengths–Opportunities (S-O) combination, indicating an aggressive and proactive approach. The S-O strategy refers to leveraging strengths or advantages to seize and capitalize on available opportunities. The suggested operational steps include (1) intensification and extensification; (2) adding tax payment channels; (3) integration/data exchange with other government agencies; (4) intensification of law enforcement cooperation; (5) strengthening regional tax regulations; and (6) improving the quality of human resources. While numerous studies have addressed regional tax management, this research is novel in its focus on developing regional tax enhancement strategies through a comprehensive SWOT analysis.